Polyvictimization, social relationship quality, and depressive symptoms in later life. - Ren, Jinnan; Ferraro, Kenneth F (Gerontologist, 2026)
Background and Objectives Drawing from stress process theory, we examine whether polyvictimization influences older adults' depressive symptoms and whether social relationship quality moderates this relationship. Research Design and Methods We used data from the Health and Retirement Study (HRS) and included 12,497 respondents for cross-sectional analyses at T1 and 11,373 respondents for longitudinal analyses at T2. Victimization was categorized into 3 levels: none, monovictimization, and polyvictimization. Relationship quality was measured by social support and social strain. Depressive symptoms were assessed using a shortened version of the CES-D (Center for Epidemiologic Studies Depression) scale. Results Monovictimization and polyvictimization were conditionally associated with more depressive symptoms at T1 and T2. At T1, polyvictimized older adults with higher support had fewer depressive symptoms compared with those with lower support. Higher social strain exacerbated depressive symptoms among monovictimized individuals. At T2, social support no longer had a moderating effect, but social strain continued to exacerbate depressive symptoms for both monovictimized and polyvictimized individuals. Discussion and Implications Polyvictimization is a potential risk factor for depressive symptoms in later life. Social support is protective, but its effect is transient. Social strain amplifies the deleterious effects of victimization on depressive symptoms over time.